Iklim Organisasi dan Kesannya ke atas Kepuasan Kerja - Khalid Gazi, Haji Ali (1999)
This study trying to examine the relationship and the effect of organizational climate toward job satisfaction among operators in a factory at Kulim High Technology Park (Kulim Hi-Tech), Kedah. The study was done in three factory at Fase One with 213 sample has take part. Four organizational climate dimensions was examined as independent variable, that is organizational culture, organizational structure, individual characteristic and ecology. The study trying to examined the relationship and the effect all this four dimensions toward the dependent variable, job satisfaction. Through correlation and regression analysis, all the five null hypotheses was rejected. Overall, the finding of this study found that organizational climate has a positive relationship with job satisfaction. The effect all the four dimensions was found significant, with the ecology factor was the dominant factor toward job satisfaction. Then followed by the individual characteristic, organizational structure and finally organizational culture. This study also gives few suggestions for future studies especially on the dimensions that to be stressed in term to upgrade the effectiveness of the organizational climate and its relationship with the job satisfaction.